Analysis of the impact of CO2 content on the physical properties of the liquid phase mixtures in oil production wells. (2017) - Zhang, Jiaming; Wu, Xiaodong; Chen, Zhangxin; Wang, Jingyao; Ren, Zongxiao
CO2 injection not only enhances oil recovery dramatically, but it also has a potential to reduce the greenhouse effect. During the process of CO2 displacement, when CO2 breaks through in oil production wells, CO2 content will impact the phase state and physical properties of the liquid phase mixture in wellbore. As a result, it will affect the calculation of temperature and pressure in oil production wells. Therefore, it is unacceptable to use the conventional black-oil model for calculating the phase state of miscible fluids. For dealing with this problem, we use a gas-liquid flash theory and a compositional model to develop a new model. The Jilin oilfield is used as a case study; the phase state (gas, liquid or gas-liquid) and physical properties of the liquid phase mixture (including CO2 and hydrocarbons) under initial conditions are calculated by this new model. The results indicate that the molar content of CO2 has a great impact on the physical properties of the liquid phase mixture in oil production wells under certain temperature and pressure. A scientific guide for the calculation of temperature and pressure in oil production wells can be provided with the developed model.